From fact to fiction - Blake, Jason (ELOPE (Ljubljana), 2004)
The title of Alice Munro's Who do you think you are? could just as easily be asked of Canada, without eliciting an easy answer. In ethnic, linguistic, evengeographical terms, Canada is hardly homogeneous. Because of this, we can only dream of a unifi ed identity; we are, as Leonard Cohen writes in Beautiful Losers, condemned to "nightmares of identity". If Canada is too complex for a uniform national identity, one derived from a convenient mythology and distilled into simple symbols, it often seems we have yet to realize it. We long for a mythology, even a modern, and blatantly constructed one. In contemporary Canadian society, ice hockey has filled that symbolic role, serving as a mythology that binds a fragmented people. This paper examines the role of ice hockey as a mythologized symbol of Canadian unity in literature, and questions the appropriateness of that usage.
Keywords: hokej na ledu; Kanada; kanadska književnost; mitologija